2017
DOI: 10.1017/s2040174417000435
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of adults’ body mass index and the association with index child’s infant birth weight, in the Lifeways Cross-Generation Cohort Study of a thousand families in the Republic of Ireland

Abstract: The Lifeways study is novel in having information on three generations of the same families. It is well established that infant birth weight (IBW) predicts individuals' risk of adult chronic disease and more recently studies report cross-generation transmission of risk patterns. The aims of this analysis were to examine whether adults' birth weights were associated with measures of own health status or social position and to relate adults' birth weights to that of the index child's IBW. Finally, we assessed wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The available studies have examined the impact of obesity over three generations by evaluating the offspring’s BMI [ 16 , 18 ] and central adiposity [ 17 ] in childhood, and the risk of excess weight (BMI > 95th percentile) up to adolescence [ 15 ]. Our study shows an impact of the grandparental obesity grade on the offspring’s BMI beyond adolescence, which supports the transgenerational transmission of the obesity cycle up to three generations and its maintenance in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available studies have examined the impact of obesity over three generations by evaluating the offspring’s BMI [ 16 , 18 ] and central adiposity [ 17 ] in childhood, and the risk of excess weight (BMI > 95th percentile) up to adolescence [ 15 ]. Our study shows an impact of the grandparental obesity grade on the offspring’s BMI beyond adolescence, which supports the transgenerational transmission of the obesity cycle up to three generations and its maintenance in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…However, Freeman et al [ 9 ] showed that having an overweight or obese father, but a mother of healthy weight, increased the probability of the offspring’s obesity in childhood, suggesting that fathers might also be a key influence. In addition, some studies have been carried out, analyzing the information of three generations (i.e., grandparents, parents, and the offspring) [ 14 , 15 , 16 , 17 , 18 ]. Davis et al [ 15 ] showed grandparental obesity to be associated independently from parental obesity with an increased prevalence of overweight individuals among children aged 5 to 19 years, in a US national sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the contribution of the VEGI subscale to the variance in BMI is very small (4%). However, it is important to acknowledge that BMI is multifactorial (Löffler et al, 2017;McKey et al, 2017), thus is difficult for a single factor to explain a large variance percentage. Although it might be possible that food disgust can contribute to adiposity in some populations, only the VEGI subscale was able to predict the increase in BMI in urban Mexican adults.…”
Section: Discussionmentioning
confidence: 99%
“…The Lifeways cross-generation cohort study in the Republic of Ireland provides the potential to examine cross-generational effects of such period exposures for Irish people over the twentieth century, especially those born and raised during the establishment of the Irish Free State and Emergency Powers Act in the WWII period. This is a three generation cohort study established a priori to examine cross-generational influences on the proband children (index-child) recruited during pregnancy in 2001–3 and several previous analyses have shown grand-parental influences on children’s outcomes ( Kelleher et al, 2014 , McKey et al, 2017 , Murrin et al, 2012 , Shrivastava et al, 2012 , Shrivastava et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%